TENSIONES GENERADAS ENTRE EL DERECHO A LA VIVIENDA DIGNA Y LAS NORMAS DE PROTECCIÓN AL CONSUMIDOR INMOBILIARIO DESDE LA INTERPRETACIÓN CONTRACTUAL (2016)
This article is a review of the major hermeneutics developments that has brought the engagement with the real estate consumer in the light of the right to adequate housing, making a tour of the doctrine, policy and national jurisprudence. The right to adequate housing has contributed constitucional sensitivy to the consumer Right, thanks to the constitutionalization of private law that has recognized the guardianship judge as guarantor of relations generated even by individuals, where the Civil Code is no longer the normative regulation center of the generated relations between them.